Analisis Bentuk Pertanggungjawaban Pihak Maxim Dalam Sebuah Perjanjian Kemitraan di Kota Gorontalo - Putri Handayani; Weny Almoravid Dunga; Waode Mustika (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the problems that occurred on maxim's side in 2023, namely the drivers who demanded maxim's policies which were considered detrimental. The existence of this problem attracts researchers to carry out research related to the form of maxim's accountability to the driver in the partnership agreement. The approach in this research uses empirical legal research, which is research that examines factual contact on every particular event that occurs in society in order to achieve the specified goals. The result of this study is the form of legal protection given by Maxim to the drivers, namely legal protection in the form of accident insurance by Yayasan Driver Sehat Sejahtera Indonesia (YPSSI) which is borne directly by Maxim and the accountability given by maxim, namely in the form of providing good services in the functional process of the application and carrying out the obligations stated in the agreement text between Maxim and the Driver.